(untitled) (Research, Society and Development, 2022)
Allelopathy is considered a naturally occurring event, which results in the release of chemical substances and/or secondary metabolisms distributed in various concentrations in the various vegetative organs of plants during their life cycle and can inhibit the physiological development of other species. A species Croton heliotropiifolius Kunth, belongs to the family Euphorbiaceae, has been indicated as a precursor of the allelopathic effect. Being assim é primordial or conhecimento in order to assist in the better development of the ecosystem. In this context, or present work, the objective was to carry out a qualitative phytochemical investigation of the foliar extract of the Croton heliotropiifolius Kunth species, as well as its allelopathic effect on the development of Lactuca sativa. The experiment was carried out at the Natural Resources Laboratory of the Federal University of Alagoas. The foram extracts obtained by decoction and subsequently evaluated qualitatively through phytochemical prospecting, followed by physical chemical characterization. No germination bioassay prepared solutions in concentrations of 0.1; 0.25; 0.5 and 1 mg/mL, I have distilled water as control. The containers were covered with germinating paper, applied 7 mL of solutions and distributed 25 seeds of L. sativa. The experimental design was entirely random, with four repetitions. The results show allelopathic potentialities of the extract of C. heliotropiifolius on the cultivar L. sativa, showing that the tannin, phenolic and flavonoid composts stimulate root elongation from a dose of 0.1 mg/mL. Therefore, the extract from C. heliotropiifolius does not cause a reduction in the germination of alpha seeds, characterizing it as a beneficial allelopathic effect.